A new species of Begonia (Begoniaceae) from Sagea Lagoon, Weda Bay, Halmahera Island, North Moluccas, Indonesia - Harry Wiriadinata (REINWARDTIA, 2012)
A new species of Begonia sageaensis Wiriadinata (Begoniaceae) from south of Mt. Sohra Ecoregion, Sagea Lagoon, Weda Bay, Halmahera, North Moluccas, Indonesia is described and illustrated. This species close to B. holosericea Teijsm. & Binn. in small herb habit but it differ in red hirsute hairs on both leaf surface and on its petiole, persistence equitant bracts, longer pedicels of male flowers andÂ  fruit has three equal wings with both flat ends.